Effects of food‐borne nanomaterials on gastrointestinal tissues and microbiota - Bouwmeester, Hans (Wiley Interdiscip Rev Nanomed Nanobiotechnol, 2017)
Ingestion of engineered nanomaterials is inevitable due to their addition to food and prevalence in food packaging and domestic products such as toothpaste and sun cream. In the absence of robust dosimetry and particokinetic data, it is currently challenging to accurately assess the potential toxicity of food‐borne nanomaterials. Herein, we review current understanding of gastrointestinal uptake mechanisms, consider some data on the potential for toxicity of the most commonly encountered classes of food‐borne nanomaterials (including TiO(2), SiO(2) (,) ZnO, and Ag nanoparticles), and discuss the potential impact of the luminal environment on nanoparticle properties and toxicity. Much of our current understanding of gastrointestinal nanotoxicology is derived from increasingly sophisticated epithelial models that augment in vivo studies. In addition to considering the direct effects of food‐borne nanomaterials on gastrointestinal tissues, including the potential role of chronic nanoparticle exposure in development of inflammatory diseases, we also discuss the potential for food‐borne nanomaterials to disturb the normal balance of microbiota within the gastrointestinal tract. The latter possibility warrants close attention given the increasing awareness of the critical role of microbiota in human health and the known impact of some food‐borne nanomaterials on bacterial viability. WIREs Nanomed Nanobiotechnol 2018, 10:e1481. doi: 10.1002/wnan.1481 1.. Toxicology and Regulatory Issues in Nanomedicine > Toxicology of Nanomaterials.